Fe-Kuala Kangsar clay as heterogeneous catalyst for fenton-like decolorization of dyeing wastewater / Hamizura Hassan and Wan Zuraida Wan Kamis - Hassan, Hamizura; Wan Kamis, Wan Zuraida (Research Management Institute (RMI), 2012)
Dyes in wastewater can create aesthetic problems, limit the possible use of water and obstruct the light penetration and oxygen transfer into water bodies, hence affecting the aquatic life. The Fenton process has long-established credibility in the field of environmental remediation for nonbiodegradable pollutants. However, the overall efficiency of homogeneous Fenton is limited with significant disadvantages like generated iron hydroxide sludge and tight range of pH. Heterogeneous Fenton emerged as an interesting ways to overcome these limitations by the usage of Fenton-like heterogeneous catalyst. In heterogeneous solid catalyst, the iron species is "immobilized" on the solid supports or within the structure and in the pore/interlayer of the catalyst. Being inexpensive and widely available, clays represents an attractive supports for iron immobilization. Therefore this study focuses on the development of heterogeneous catalysts from the low cost material, which is Kuala Kangsar clay. The efficiency of this heterogeneous catalyst will be tested on decolorization of model real textile wastewater that is Reactive Black 5 (RB5) by making use of a Fenton-like process. This catalyst (Fe-Kuala Kangsar clay) will be prepared by impregnation method in which iron ion act as catalyst is attached on the supported catalyst (Kuala Kangsar clay). The prepared catalyst is characterized by using Scanning Electron Microscope (SEM), Brunauer Emmett-Teller (BET), Fourier Transform Infrared (FTIR), Elemental chemical analysis (EDX), and X-Ray diffraction (XRD). The effect of different reaction parameters such as different ion loading on supported catalyst, catalyst dosage, initial pH, and initial concentration of hydrogen peroxide and dye on the decolorization of RB5 will be assessed. It is expected that Fe- Kuala Kangsar clay catalyst possess a potential to treat RB 5 solution and this could give an added value since it is natural, abundant, low cost and environmentally friendly.